Computer Vision Applications in Garbage Management: A Survey - Li, Yiyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, computer vision (CV) technique has made great breakthroughs, and it has been applicated in the fields related to garbage management. Due to quick expansion of consumerism and urbanization, the amount of garbage generated by humans has increased rapidly, which has caused harmful results for both the environment and people’s lives. Identifying garbage automatically by means of CV technique plays an important role in urban road garbage detection, marine litter detection and garbage classification. This paper, gathering research from various sources, show how computer vision techniques can help garbage management to become smarter and more accurate by giving a view of the literature on different CV applications in the fields related to garbage management. In addition, the paper also aims to find and analyze the common problem when practicing the theories in practice and several promising directions for future research.